2020
DOI: 10.1101/2020.09.05.284349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CASCADES, a novelSOX2super-enhancer associated long noncoding RNA, regulates cancer stem cell specification and differentiation in glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common primary malignant brain tumor in adults, with a median survival of just over one year. The failure of available treatments to achieve remission in patients with GBM has been attributed to the presence of cancer stem cells (CSCs), which are thought to play a central role in tumor development and progression and serve as a treatment-resistant cell repository capable of driving tumor recurrence; in fact, the property of "stemness" itself may be responsible for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The other regulatory mechanisms are also involved in SOX /lncRNA interplay in GBM ( Table 2 , Figure 3 ). LncRNA CASCADES is a SOX2 super-enhancer-associated lncRNA [ 85 ]. Super-enhancers represent clusters of enhancers in close genomic proximity that can work as independent regulatory regions or as a part of a large transcription regulatory network to enable the gradient expression of genes they regulated [ 95 , 96 ].…”
Section: Lncrnas Acting Through Sox Genes In Gliob...mentioning
confidence: 99%
See 3 more Smart Citations
“…The other regulatory mechanisms are also involved in SOX /lncRNA interplay in GBM ( Table 2 , Figure 3 ). LncRNA CASCADES is a SOX2 super-enhancer-associated lncRNA [ 85 ]. Super-enhancers represent clusters of enhancers in close genomic proximity that can work as independent regulatory regions or as a part of a large transcription regulatory network to enable the gradient expression of genes they regulated [ 95 , 96 ].…”
Section: Lncrnas Acting Through Sox Genes In Gliob...mentioning
confidence: 99%
“…Super-enhancer-associated lncRNAs, lncRNAs transcribed from super-enhancers, have emerged as master regulators of cell fate determination and differentiation since they regulate the expression of genes essential for these processes by transcription factor trapping, chromatin modifications, recruitment of the RNA Pol II complex, and removal of the co-repressor function [ 98 , 99 ]. Shahzad et al discovered lncRNA CASCADES transcribed from a distal super-enhancer of SOX2 [ 85 ]. They revealed that CASCADES is an epigenetic regulator of SOX2 in GSCs and an essential factor for the maintenance of stemness in these cells [ 85 ].…”
Section: Lncrnas Acting Through Sox Genes In Gliob...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent study identified a lncRNA, Cancer stem cell associated distal enhancer of SOX2 ( CASCADES ) as a novel epigenetic regulator for glioma cancer stem cells (GCSCs) (Shahzad et al, 2020 ). Hi-C mapping revealed the CASCADES intronic enhancer interacted with SOX2 promoter in GCSCs.…”
Section: Regulation Of Csc Plasticity By Chromatin Topologymentioning
confidence: 99%